Conservation and Exploration of the Potential of Rare Medicinal Plants in the Tropical Rainforest of Bukit Barisan, Sumatra, Indonesia: An Effort Towards Sustainable Herbal Medicine - Maulana, Syaidina (HM Publisher, 2024)
The Bukit Barisan tropical rainforest in Sumatra, Indonesia, is one of the most biodiverse areas in the world. It is estimated that there are more than 10,000 plant species in this forest, and many of them have potential as herbal medicines. However, deforestation and overexploitation threaten the preservation of medicinal plants in the Bukit Barisan tropical rainforest. This causes loss of valuable natural resources and hinders research and development of new herbal medicines. This research was conducted in several tropical rainforests in Bukit Barisan, Sumatra. Field surveys were conducted to document rare medicinal plant species. Plant samples were collected and analyzed for their phytochemical content. Bioassay tests were carried out to evaluate antibacterial, antioxidant and anti-inflammatory activities. Strategies for conservation and sustainable exploration of rare medicinal plants are developed based on research results. Field surveys found 27 species of rare medicinal plants. Phytochemical analysis shows that this plant contains various bioactive compounds, such as alkaloids, flavonoids and terpenoids. Bioassay tests show that this plant has significant antibacterial, antioxidant and anti-inflammatory activity. In conclusion, the Bukit Barisan tropical rainforest has great potential for the development of herbal medicine. Sustainable conservation and exploration of rare medicinal plants in the Bukit Barisan tropical rainforest is important to ensure the preservation of these valuable natural resources and to improve community health.